Formulation and evaluation of ophthalmic microemulsion for enhanced topical administration of brinzolamide - Zafar, Sehrish; Nazar, Muhammad Faizan; Siddique, Muhammad Yasir; Haider, Sajjad; Alam, Kamran; Saleem, Muhammad Atif; Shaukat, Saadia; Abd Ur Rahman, Hafiz Muhammad; Ullah, Zaka (Frontiers in Materials, 2024)
Microemulsions (μEs) are more effective than conventional formulations for ophthalmic use due to their optical transparency, thermodynamic stability, structural flexibility and higher bioavailability. In addition, μE formulations can increase the water solubility of the drug and improve drug absorption in the eye. Herein, we report the development of three new biocompatible μE formulations containing an antihypertensive drug brinzolamide (BZD) and their evaluation for topical ocular administration. For this, Formulations A, B and C were optimized using an appropriate ratio of isopropyl myristate (IPM) as oil phase, water as aqueous phase and 2-propanol as co-surfactant, while Tween-80, Tween-20 and Tween-60 were selected as surfactant for each formulation, respectively. Preliminary, pseudoternary phase diagrams were delineated and then electrical conductivity and optical microscopy were used to establish optimal formulation for each μE to upheld the appropriate amount of BZD, i.e., 2.0 wt. %, 2.0 wt. %, and 1.0 wt. % in formulation A, B and C, respectively. Dynamic light scattering demonstrated very fine monomodal assembly of BZD-μE nanodroplets (~50 nm), while FTIR analysis showed effective encapsulation of BZD into hydrophobic microenvironment with no observable chemical interaction between BZD and μE excipients, which was further verified by the peak-to-peak concomitant measurement of fluorescence.Further, in-vitro release of BZD-μE showed enhanced and persistent topical ocular administration (> 99%) within 10 hours demonstrating the appropriate formulation for topical instillation.